Pain levels and associated factors in the Scleroderma Patient-centered Intervention Network (SPIN) cohort: a multicentre cross-sectional study. (December 2021) - Lee, Yvonne C; Fox, Rina S; Kwakkenbos, Linda; Levis, Brooke; Carrier, Marie-Eve; Welling, Joep; Sauvé, Maureen; Mouthon, Luc; Benedetti, Andrea; Bartlett, Susan J; Varga, John; Thombs, Brett D; et al.
Summary: Background: Pain is an important and detrimental feature of systemic sclerosis but is often overlooked or deprioritised in research and clinical care. Raynaud's phenomenon, arthritis, and cutaneous ulcers are among the commonly reported disease manifestations of systemic sclerosis that could be associated with pain. We aimed to assess levels of pain intensity and interference and to evaluate disease factors associated with pain intensity and interference. Methods: In this multicentre cross-sectional study, participants from the Scleroderma Patient-centered Intervention Network cohort who completed pain intensity and interference measures (Patient Reported Outcomes Information System-29 profile, version 2·0) as part of baseline assessments were included. Patients were recruited from 46 centres in Australia, Canada, France, Mexico, Spain, the UK, and the USA between April 15, 2014, and Jan 7, 2020. Eligible patients included those aged 18 years or older who met the criteria for systemic sclerosis devised by the American College of Rheumatology and the European League Against Rheumatism. Associations of pain intensity and pain interference with systemic sclerosis-related variables and overlap syndromes, controlling for sociodemographic variables, were assessed with multiple linear regression. Continuous independent variables were standardised. Findings: Among 2157 participants with systemic sclerosis (268 [12%] males and 1889 [88%] females), 1870 (87%) reported mild, moderate, or severe pain (defined as ≥1 on a 0 to 10 scale), and 815 (38%) reported moderate or severe pain (defined as ≥5). Moreover, 757 (35%) participants reported moderate or severe pain interference. Greater pain intensity was independently associated with female sex (0·58 points [95% CI 0·26–0·90]), non-White race or ethnicity (0·50 points [0·21–0·79]), fewer years in formal education (0·30 points per SD [0·19–0·41]), country (reference: USA; Canada: 0·29 points [0·01–0·57] and UK: 0·58 points [0·21–0·95]), greater body-mass index (0·35 points per SD [0·24–0·45]); joint contractures (0·67 points [0·39–0·94]), digital ulcers (0·33 points [0·10–0·55]), gastrointestinal involvement (0·66 points [0·33–0·98]), skin involvement (measured using modified Rodnan skin score; 0·22 points per SD [0·10–0·35]), rheumatoid arthritis (0·96 points [0·50–1·43]), and Sjögren's syndrome (0·42 points [0·01–0·83]). Pain interference results were similar. Interpretation: Pain is common among people with systemic sclerosis. Controlling for sociodemographic variables, greater pain was associated with multiple systemic sclerosis-related manifestations, including joint contractures, digital ulcers, gastrointestinal involvement, skin involvement, and the presence of overlap syndromes. Health-care providers should work with patients to address pain, including identifying and addressing systemic sclerosis manifestations associated with their pain, and supporting behavioural approaches to minimise impact on function and quality of life. Funding: Canadian Institutes of Health Research, Arthritis Society, The Lady Davis Institute for Medical Research of the Jewish General Hospital, Jewish General Hospital Foundation, McGill University, Scleroderma Society of Ontario, Scleroderma Canada, Sclérodermie Québec, Scleroderma Manitoba, Scleroderma Atlantic, Scleroderma Association of BC, Scleroderma SASK, Scleroderma Australia, Scleroderma New South Wales, Scleroderma Victoria, and Scleroderma Queensland.